Cryptography and information security in the Balkans : first international conference, BalkanCryptSec 2014, Istanbul, Turkey, October 16-17, 2014, Revised selected papers /: first international conference, BalkanCryptSec 2014, Istanbul, Turkey, October 16-17, 2014, Revised selected papers. (2015) - Unknown
No abstract available